Study the Effect of Quenching and Tempering Conditions on the Fatigue Coefficients for Low Carbon Steel - Hassan, Azzam D.; Almtori, Safaa A. S.; Nema, Atef (Basrah Journal for Engineering Sciences, 2022)
Four groups of AISI 1020 specimens were heat-treated at 850 °C in a muffle furnace for 30 minutes then quenched in oil. The samples were tempered at 400 °C with a time period for each group as (group B, 2 hours), (group C, 3 hours), and (group D, 4 hours). The mechanical properties of the samples were studied using universal tensile testing equipment and a Brinell hardness testing machine. The hardness values of the quenched samples were calculated from a given modified equation. The torsional fatigue behavior of AISI 1020 was discovered in this investigation for heat-treated specimens and compared with the original specimens. All groups were subjected to an analysis using an optical microscope. Pearlite is formed when is heated in the austenitic region and then cooled below a lower critical temperature. It was concluded that the heat treatment increases the hardness for the specimens while decreased the shear fatigue ductility coefficient. Also, the heat treatment increased the shear fatigue strength coefficient. Furthermore, increasing in the time period of the tempering process was leaded to decrease the coefficient of shear fatigue strength and increased the coefficient of shear fatigue ductility.